Psychopathology of rare and unusual syndromes - Oyebode, Femi (Cambridge University Press, 2021)
Rare and unusual psychiatric syndromes have fascinated people for centuries due to their complexity and undefined nature. Appreciating their clinical importance and relevance to understanding other conditions and experiences, this book provides an authoritative account of the rarest and most unusual psychiatric syndromes. The author, a leading authority on clinical psychopathology, delves into the history of the description of such syndromes, illustrates conditions with clinical case examples, and discusses the causes as well as the underlying explanatory mechanisms. The syndromes described draw attention to the way in which abnormal subjective experiences reflect the intersection of biomedical science, social anthropology, social sciences, evolutionary biology and the humanities. The book covers abnormalities of belief, abnormalities of perception, unusual experiences of the body and self, rare and bizarre impairments of memory, and behavioural disturbance. This is a valuable resource for psychiatrists, as well as researchers interested in the relationship between psychiatry and other disciplines.